Rif1 acts through Protein Phosphatase 1 but independent of replication timing to suppress telomere extension in budding yeast - Kedziora, S; Gali, V; Wilson, R; Clark, K; Nieduszynski, C; Hiraga, S; Donaldson, A (Oxford University Press, 2018)
The Rif1 protein negatively regulates telomeric TG repeat length in the budding yeast Saccharomyces cerevisiae, but how it prevents telomere over-extension is unknown. Rif1 was recently shown to control DNA replication by acting as a Protein Phosphatase 1 (PP1)-targeting subunit. Therefore, we investigated whether Rif1 controls telomere length by targeting PP1 activity. We find that a Rif1 mutant defective for PP1 interaction causes a long-telomere phenotype, similar to that of rif1Δ cells. Tethering PP1 at a specific telomere partially substitutes for Rif1 in limiting TG repeat length, confirming the importance of PP1 in telomere length control. Ablating Rif1-PP1 interaction is known to cause precocious activation of telomere-proximal replication origins and aberrantly early telomere replication. However, we find that Rif1 still limits telomere length even if late replication is forced through deletion of nearby replication origins, indicating that Rif1 can control telomere length independent of replication timing. Moreover we find that, even at a de novo telomere created after DNA synthesis during a mitotic block, Rif1-PP1 interaction is required to suppress telomere lengthening and prevent inappropriate recruitment of Tel1 kinase. Overall, our results show that Rif1 controls telomere length by recruiting PP1 to directly suppress telomerase-mediated TG repeat lengthening.